UPTAKE OF NUTRIENTS BY WHEAT AS INFLUENCED BY LONGTERM PHOSPHORUS FERTILIZATION - SAHA, BHOLANATH; SAHA, SUSHANTA; PODDAR, PARTHENDU; SIDHU MURMU; A. K. SINGH (The Bioscan, 2013)
The study was undertaken to monitor the fate of applied P into its nutrition using a 40 years old long-term fertility experiment started since rabi 1968-69 with pearl millet-wheat cropping system for the present investigation during 2009 and 2010. All the water soluble phosphatic fertilizers (SSP, DAP, UAP) were found significantly superior over partially water soluble (nitrophosphate) and mineral acid soluble (RP) sources in terms of nutrients uptake by wheat. On an average, 45 to 55% increase of N, P and K uptake were found upon application of water soluble phosphatic fertilizers over mineral acid soluble sources viz. RP. With increasing levels of P from 60 to 120 kg P2O5 ha-1, N, P, K and Mn uptake increased significantly, whereas, Fe, Zn and Cu uptake decreased significantly. The increase of 25.6 and 32.4 kg ha-1 N uptake, 4.9 and 6.5 kg ha-1 P uptake and 28.1 and 36.9 kg ha-1 K uptake was recorded with the application of 60 and 120 kg P2O5 ha-1 phosphatic fertilizers, respectively, over control. Cumulative mode of P application was found the best for NPK and Mn uptake by wheat as compared to direct and residual mode.